A role for nurses during echocardiography procedure in ethnically sensitive settings - Aburawi, Elhadi; Mohammad, Ekhlass (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Echocardiography is the main procedure for diagnosis in both acquired and congenital heart diseases (CHD). In pediatric cardiology, the surgeons accept more than 80% of children with CHD for surgery just based on echocardiography investigation. The role of nurses before, during, and after the procedure is well known since 1982. Their role is becoming more and more challenging with the development of technology and easier manipulation during echocardiography procedure. In this practice point, we are highlighting a new role for female cardiac nurses in the outpatient clinical setting. This new nurse's role is to handle the probe during the echocardiography procedure for the adolescent girls by a female nurse.
Keywords: Echocardiography; education; ethnicity; focused cardiac ultrasound; healthcare access; nurse screening